Penegakan Hukum Pidana Terhadap Pelaku Korupsi Dana Hibah Pilkada - Warawarin, Fernando Fiki; Hehanussa, Deassy Jacomina Anthoneta; Hattu, Jacob (MATAKAO Corruption Law Review, 2025)
Introduction: Corruption is an extraordinary crime that causes significant losses to state finances and undermines the democratic order. The corruption case involving five members of the local General Elections Commission (KPU) in the 2020 Aru Islands Regency election grant fund has drawn attention due to its direct link to the misuse of state funds in organizing the democratic process. Purposes of the Research: To study and analyze the enforcement of criminal law against perpetrators of corruption of regional election grant funds in the Aru Islands Regency. Methods of the Research: The research method used was empirical legal methodology supported by a normative approach. Primary data was obtained through interviews with judges from the Corruption Crimes Division of the Ambon District Court, while secondary data were obtained through literature review and documentation. Data analysis was conducted using descriptive qualitative methods. Results of the Research: The results indicate that criminal law enforcement in this case was carried out through the stages of inquiry, investigation, prosecution, and court decision. The defendants were sentenced to one year and six months in prison, fined, and required to pay restitution to the state. However, the principle of ultimum remedium was not applied, as corruption is considered a serious crime, thus placing criminal law as the primum remedium. Influencing factors were the magnitude of the state losses, abuse of authority by public officials, and the impact on public trust in local democracy.